Pengaruh Kompetensi, Independensi, Profesionalisme Dan Pengalaman Kerja Terhadap Kualitas Audit Dengan Etika Auditor Sebagai Variabel Moderating(Studi Empiris pada Kantor Akuntan Publik di Surakarta dan Yogyakarta) - Khoirul Maulana, Miftah, Dr. Fatchan Achyani, M.Si (2015)
The objectives of this research to empirically analyze the influence of competency, independency, professionalism and experience work on audit quality, and to the influence of competency, independency, professionalism and experience work to audit quality is moderated by auditor ethics, especially in the auditor working in KAP Surakarta and Yogyakarta. The population in this research are all auditors who worked on the KAP in Surakarta and Yogyakarta. Sampling was conducted using a purposive sampling method and number of samples of 49 respondents. Primary data collection method used is questionnaire method. The data are analyzed by using technical analyze Multiple Regression Analyze and Moderate Regression Analyze (MRA). The result showed that the variable competence, the interaction competence and auditor ethics and the interaction independence and auditor ethics have no effect on audit quality. While the variable independence, professionalism, experience work, the interaction professionalism and auditor ethics and the interaction experience work and auditor ethics have effect on audit quality.